Effects of China's pilot low-carbon city policy on carbon emission reduction: A quasi-natural experiment based on satellite data - Huo, Weidong; Qi, Jie; Yang, Tong; Liu, Jialu; Liu, Miaomiao; Zhou, Ziqi (Technological forecasting & social change, 2022)
•Fresh emission data calculated by satellite to probe CO2 reduction in China 2005–2017.•Effects of low-carbon-city pilot implementation probed using a DID method.•Emission reduction in resource-based cities exceed that in non-resource-based ones.•The low-carbon-city policy caused a GDP loss of 1.19 trillion yuan in 2013–2017. Economic development has brought about global greenhouse gas emissions and thus global climate change, which is a common challenge for all mankind that urgently needs to be addressed. As the focal points of national economic development, cities have major responsibilities with regard to low-carbon development and climate change mitigation and adaptation. Countries around the world are actively exploring low-carbon development. In response to climate change, China has actively explored and adopted pilot policies for low-carbon cities, to reduce carbon emissions and mitigate climate change. In this study, we used a differences-in-differences approach to explore the effects of emission reduction and conducted a cost-benefit analysis of the pilot cities. The empirical results showed that pilot cities reduced carbon emissions annually by approximately 2.72%. Additionally, the associated gross domestic product loss from 2013 to 2017 was approximately 1.19 trillion yuan. Mechanism analysis elucidated that pilot cities reduced emissions by adjusting their industrial structure, promoting technological innovation of enterprises to increase their total-factor productivity, and stimulating research and development of low-carbon technologies. The results of this study provide examples, supported by data, for the government to further promote the low-carbon city construction policy.